PF-15 Surgical Management for Medial Patellar Luxation with Trochlear Block Recession and Lateral Imbrication Methods in Labrador Retriever Dog - Siti Zaenab; Ivan Satriawan; Eva Zulfiati; Sukmasari Arifah; Benda A Suwito (Hemera Zoa, 2018)
Medial patellar luxation is a displacement of the patella from the trochlear sulcus[1]. Medial patellar luxation is one of the common cause of lameness in small-breed dogs, but it also occurs in large-breed dogs[1]. This case report will reveal how to diagnose and treat medial patellar luxation